REVIEW. Streptococcus thermophilus bacteriophages - Quiberoni, Andrea del Lujan (2010)
For several decades, lactic acid bacteria have been extensively used on an industrial scale in the food industry. This success also created several technological problems, bacteriophage contamination being one of the most acute. Over the last 55 years, studies from Europe, North America, and Argentina reported the isolation of at least 345 bacteriophages infecting Streptococcus thermophilus starter cultures. Of the various milk fermentation processes, cheese making is by far the most sensitive to phage infections. High thermal resistance, short latent periods and large burst size were reported for these bacterial viruses. Phages with such characteristics are primed to thrive in this dynamic environment, lysing bacterial cultures and generating low-quality fermented products. To date, all S. thermophilus phages are members of the Siphoviridae family and the Caudovirales order. Their double-stranded DNA genomes vary from 29 to 43 kbp in size. The phages seem to be related in various ways and appear to constitute a polythetic phage species that is divided in two large groups based on the mode of DNA packaging, named cos and pac types, respectively. Comparative analyses have shown that S. thermophilus phage genomes are similarly organized into distinct modular regions and allow the detection of a core genome region.  Several PCR-based techniques have been designed to detect them in cheese whey and milk samples. Similar S. thermophilus phages are globally distributed and endemic in specific dairy environments. The biogeography of S. thermophilus phages reinforces their current classification.